Show that the partial differential equations
z = px + qy and 2xy(p2 + q2) = z(yp + xq)are compatible
Two PDEs "f,g" are compatible if they have a common solution. We must show that,
"[f,g]=\\frac{\\partial (f,g)}{\\partial (x,p)}+p\\frac{\\partial (f,g)}{\\partial (z,p)}+\\frac{\\partial (f,g)}{\\partial (y,q)}+q\\frac{\\partial (f,g)}{\\partial (z,q)}=0"
"z=px+qy..................................................(1)\\\\\n\\text{Let }f=z-px-qy=0\\\\\n2xy(p^2+q^2)=z(yp+xq)............................(2)\\\\\n\\text{Let }g=2xy(p^2+q^2)-z(yp+xq)=0".
We shall compute the expression for "\\frac{\\partial f}{\\partial x},\\frac{\\partial f}{\\partial y},\\frac{\\partial f}{\\partial z},\\frac{\\partial f}{\\partial p},\\frac{\\partial f}{\\partial q}" . The same thing for "g".
"\\frac{\\partial f}{\\partial x}=-p,\\frac{\\partial f}{\\partial y}=-q,\\frac{\\partial f}{\\partial z}=1,\\frac{\\partial f}{\\partial p}=-x,\\frac{\\partial f}{\\partial q}=-y\\\\\n\\frac{\\partial g}{\\partial x}=2y(p^2+q^2)-zq,\\frac{\\partial g}{\\partial y}=2x(p^2+q^2)-zp,\\frac{\\partial g}{\\partial z}=-(yp+xq),\\frac{\\partial g}{\\partial p}=4xyp-yz,\\frac{\\partial g}{\\partial q}=4xyq-xz."
"\\frac{\\partial (f,g)}{\\partial (x,p)}=\\begin{vmatrix}\n \\frac{\\partial f}{\\partial x} & \\frac{\\partial g}{\\partial x} \\\\\n \\frac{\\partial f}{\\partial p} & \\frac{\\partial g}{\\partial p}\n\\end{vmatrix}=\\begin{vmatrix}\n -p & 2y(p^2+q^2) \\\\\n -x & 4xyp-yz\n\\end{vmatrix}=2xyq^2+yzp-2xyp^2"
"\\frac{\\partial (f,g)}{\\partial (z,p)}=\\begin{vmatrix}\n \\frac{\\partial f}{\\partial z} & \\frac{\\partial g}{\\partial z} \\\\\n \\frac{\\partial f}{\\partial p} & \\frac{\\partial g}{\\partial p}\n\\end{vmatrix}=\\begin{vmatrix}\n 1 & -(yp+xq) \\\\\n -x & 4xyp-yz\n\\end{vmatrix}=3xyp-yz-x^2q"
"\\frac{\\partial (f,g)}{\\partial (y,q)}=\\begin{vmatrix}\n \\frac{\\partial f}{\\partial y} & \\frac{\\partial g}{\\partial y} \\\\\n \\frac{\\partial f}{\\partial q} & \\frac{\\partial g}{\\partial q}\n\\end{vmatrix}=\\begin{vmatrix}\n -q & 2x(p^2+q^2) \\\\\n -y & 4xyq-xz\n\\end{vmatrix}=2xyp^2+xzq-2xyq^2"
"\\frac{\\partial (f,g)}{\\partial (z,q)}=\\begin{vmatrix}\n \\frac{\\partial f}{\\partial z} & \\frac{\\partial g}{\\partial z} \\\\\n \\frac{\\partial f}{\\partial q} & \\frac{\\partial g}{\\partial q}\n\\end{vmatrix}=\\begin{vmatrix}\n 1 & -(yp+xq) \\\\\n -y & 4xyq-xz\n\\end{vmatrix}=3xyq-xz-y^2p"
"[f,g]=2xyq^2+yzp-2xyp^2+3xyp^2-yzp-x^2pq+2xyp^2+xzq-2xyq^2+3xyq^2-xzq-y^2pq\\\\\n[f,g]=3xyp^2+3xyp^2-x^2pq-y^2pq\\\\\n[f,g]=4xyp^2+4xyq^2-xyp^2-x^2pq-xyq^2-y^2pq\\\\\n[f,g]=4(xy(p^2+q^2))-xp(yp+xq)-yq(xq+yp)\\\\\n[f,g]=2z(xp+yq)-(xp+yq)(yp+xq) \\text{ From (2)}\\\\\n[f,g]=2z(xp+yq)-z(yp+xq) \\text{ From (1)}\\\\\n[f,g]=z(yp+xq)\\neq0"
Hence, "f,g" are not compatible.
Comments
Leave a comment